Clinicopathological and prognostic significance of PKM2 protein expression in cirrhotic hepatocellular carcinoma and non-cirrhotic hepatocellular carcinoma. Issue 1 (December 2017) - Liu, Yan; Wu, Hao; Mei, Ying; Ding, Xiong; Yang, Xiaoli; Li, Changping; Deng, Mingming; Gong, Jianping
Abstract Pyruvate kinase M2 (PKM2), a key protein in glucose and lipid metabolism, has been reported to be related to carcinogenesis in various malignancies. However, its roles in hepatocellular carcinoma with cirrhotic liver (CL) and hepatocellular carcinoma with non-cirrhoticliver (NCL) haves not been investigated. In our study western bloting, qRT-PCR and immunohistochemistry were performed to evaluate the clinical significance of PKM2 protein expression in CL and NCL. The results revealed that PKM2 protein expression was significantly higher in HCC tissues than in their adjacent non-tumour tissues. The high expression rates of PKM2 were more frequently noted in CL (45. 6%) than in NCL (31. 9%) tissues. High PKM2 expression in CL and NCL tissues was significantly associated with vascular invasion (P = 0.002 and P = 0.004, respectively) and intrahepatic metastasis (P < 0.001 and P = 0.019, respectively). Importantly, Kaplan–Meier survival analysis showed that the disease-specific survival (DSS) and recurrence-free survival (RFS) were lower in CL with high PKM2 expression than in NCL with high PKM2 expression (P = 0.003 and P = 0.003, respectively). Overall, high PKM2 expression was more frequently found in CL than in NCL, and PKM2 overexpression was associated with poor survival rates in patients with CL and NCL.